Deferred tax assets, earnings quality and their effects on bank results: Evidence from Brazil - Almeida, Rodrigo Ferraz de; Monte-mor, Danilo Soares (Contextus - Revista Contemporânea de Economia e Gestão, 2024)
Background: Deferred Tax Assets (AFD) can pollute the quality of earnings by their use, as the reported earnings will be inflated by these assets, resulting from discretionary financial operations. Purpose: This study aimed to identify the effects of AFD on the perspective of earnings quality of banks, using the proxy’s earnings persistence, earnings smoothing and Earning Response Coefficient (ERC). Method: The empirical tests were based on information from the financial reports of the banks, Brazilian Central Bank (BACEN), Bloomberg and Economatica® from 2017 to 2021, being estimated using panel data. Results: The results suggest that the larger the AFD, the greater the earnings persistence and unexpected earnings by the ERC, and the lower the earnings smoothing. Conclusions: The profit quality perspective shown in the results highlights the validation of the proposed models, contributing not only to the AFD theme and the quality of profits, but also the association of the discretionary use of these assets as generators of polluting results for banks, being verified, in this study, the medium ones showed significance in the use of AFD for the persistence of profits, and the small ones for the persistence and smoothing of profits, benefiting from the movements of loans granted and AFD stocks, making them more persistent and smoothed over the sample period.